A Method of Abnormal Cell Analysis for Customer Experience Active Optimization - Gen Yuan; Tong Liu; Zhaoyang Shi (Dianxin kexue)
An innovative analysis of abnormal cell system was presented, abandoned the method of traditional macroscopic to microcosmic, directly facing the micro mobile network minimum unit “Sector Carrier”by“double cohort, the three threshold”analysis method. Performance anomaly area monitoring based on customer experience was closely related to the realization of customer experience problems, timely discovery and active optimization. Abnormal cell breaks the network quality evaluation system based on the traditional macro indicators, accounted for the abnormal cell micro level, the network quality was evaluated.